History of Transport Infrastructure in Central Asia - Rahmonkulovna, Abdusalomova Sevara (European Journal of Life Safety and Stability (2660-9630), 2023)
The collapse of the USSR and the subsequent formation of independent states with their own borders and customs led to the collapse of transport communications and a sharp increase in the problem of transit cargo delivery throughout Central Asia. The problem of developing and creating railway lines in the Central Asian region has become particularly acute. After all, valuable raw materials must be delivered to the place where they are needed. The ability to use the advantages of the geographical location of the Central Asian countries with maximum efficiency allows building modern infrastructure here and raising the standard of living of the population. And if they can diversify the directions of sale of mineral raw materials as much as possible, the mining industry will become a reliable source of savings for the general economic growth of the countries. The integration of the Central Asian republics into the world market system also solves the most important political problem. This article analyzes infrastructure issues in the region.